Blood lactate concentrations and heart rates of Colombian Paso horses during a field exercise test (2021)
ABSTRACT: Information on performance indices in Paso horses is scarce. Field exercise tests are necessary to recreate the exertion that occurs during training and competition. To describe blood lactate concentrations and heart rates of untrained Colombian Paso horses (CPHs) in response to a field exercise test. A 30-minutes-long standardized field exercise test was carried out on 11 untrained adult CPHs of both sexes. Blood lactate concentration (BLConc) and heart rate (HR) were measured before, during each step of the test, and at recovery. The BLConc and HR were used to calculate the HR at which a BLConc of 4 mmol/L or anaerobic threshold (HRL4) was reached. The HR during the field exercise test increased according to the protocol used. The BLConc during the test was variable and, despite having been increasing like the HR, the distribution of the values in each step of the test was remarkably dispersed. The mean blood lactate clearance (BLClear) percentage was 56.3 ± 16, similar in most animals. The HRL4 was reached at a notably different HR among individuals (132 to 251 bpm). The field exercise test protocol used herein is useful to assess BLConc and HR changes in acute response to exercise in CPHs. It would be useful to evaluate training kinetics with other parameters including cell blood count and muscle enzymes.